Emerging Roles of L-Type Voltage-Gated and Other Calcium Channels in T Lymphocytes - Badou, Abdallah; Jha, Mithilesh K.; Matza, Didi; Flavell, Richard A. (Frontiers in Immunology, 2013)
In T lymphocytes, calcium ion controls a variety of biological processes including development, survival, proliferation, and effector functions. These distinct and specific roles are regulated by different calcium signals, which are generated by various plasma membrane calcium channels. The repertoire of calcium-conducting proteins in T lymphocytes includes store-operated CRAC channels, transient receptor potential (TRP) channels, P2X channels, and L-type voltage-gated calcium (Cav1) channels. In this paper, we will focus mainly on the role of the Cav1 channels found expressed by T lymphocytes, where these channels appear to operate in a TCR stimulation-dependent and voltage-sensor independent manner. We will review their expression profile at various differentiation stages of CD4 and CD8 T lymphocytes. Then, we will present crucial genetic evidence in favor of a role of these Cav1 channels and related regulatory proteins in both CD4 and CD8 T cell functions such as proliferation, survival, cytokine production and cytolysis. Finally, we will provide evidence and speculate on how these voltage-gated channels might function in the T lymphocyte, a non-excitable cell.